Social efficiency of entry in a vertically related industry - Basak, Debasmita; Mukherjee, Arijit (Elsevier, 2016)
We provide a new perspective to the literature on social desirability of entry by showing that, if the input supplier has market power, social desirability of entry of the final goods producers depends on returns to scale. Entry in the final goods market can be socially insufficient under constant returns to scale technology, but it can be socially excessive under decreasing returns to scale technologies if the cost of entry is low so that the final goods market is sufficiently competitive. Hence, the anti-competitive entry regulation policies are more justifiable if the final goods market is characterised by decreasing returns to scale technologies.